Public Relations Media Creation of Ban Tro Bon Community, Sai Buri District, Pattani Province - Sengloiluean, Kittiphong; Keawpimon, Preeya; Ruangrit, Rattikarn; Kamnoedraksa, Sutinan (Journal of Information and Learning [JIL], 2022)
The objectives of this research were to create community public relations media and to investigate the satisfaction toward the public relations media of Ban Tro Bon Community in Sai Buri District in Pattani Province. Research and development methods were applied. The sample group comprised 254 members of Ban Tro Bon Community, who had watched the community public relations media. The public relations media of Ban Tro Bon Community and questionnaire about the satisfaction toward the community public relations media were used as research tools. The mean and standard deviation (S.D.) were applied to analyze the collected data. The research results showed that the overall satisfaction of the sample group toward the public relations media of Ban Tro Bon Community was at the highest level ( =4.564, S.D.=0.239). Therefore, the results of this research can be applied as a model of public relations media for other communities to publicize the community, tourism, and famous products to tourists.